GAMM Annual Meeting – München 2018, Overview of the Sections (Proceedings in applied mathematics and mechanics, 2018)
Volume 18 (2018) of PAMM “Proceedings in Applied Mathematics and Mechanics” assembles the contributions to the 89th Annual Meeting of the Gesellschaft für Angewandte Mathematik und Mechanik (GAMM), held 19 – 23 March 2018 at Technical University of Munich, Germany. The contributions are grouped according to the minisymposia and sessions of the conference. Overview of the Sections GAMM related DFG Priority Programmes PP01 Reliable Simulation Techniques in Solid Mechanics. Development of Non‐Standard Discretization Methods, Mechanical and Mathematical Analysis PP03 Property improvements of components by metal forming induced residual stresses PP04 Cyclic Deterioration of High‐Performance Concrete in an Experimental‐Virtual Lab PP05 Polymorphic Uncertainty Modelling for the Numerical Design of Structures PP06 Calm, Smooth and Smart – Novel Approaches for Influencing Vibrations by Means of Deliberately Introduced Dissipation Minisymposia MS 1 Adaptive Control with Performance Guarantees MS 2 Computational Interdisciplinary Modeling MS 3 Experimental Mechanics MS 4 High‐Performance Computing for Continuum Mechanics Problems MS 5 PDE Constrained Optimization under Uncertainty Sections 1–24 S1 Multi‐body dynamics S2 Biomechanics S3 Damage and fracture mechanics S4 Structural mechanics S5 Nonlinear oscillations S6 Material modelling in solid mechanics S7 Coupled problems S8 Multiscales and homogenization S9 Laminar flows and transition S10 Turbulence and reactive flows S11 Interfacial flows S12 Waves and acoustics S13 Flow control S14 Applied analysis S15 Uncertainty quantification S16 Optimization S17 Applied and numerical linear algebra S18 Numerical methods of differential equations S19 Optimization of differential equations S20 Dynamics and control S21 Mathematical signal and image processing S22 Scientific computing S23 Applied operator theory S24 History of fluid mechanics and history, teaching and popularization of mathematics Young Researchers' Minisymposia YR1 Isogeometric Methods YR2 Mechanics of Porous Cellular Materials YR3 Non‐Standard Mixed Finite Element Schemes for Solid Mechanics YR4 Optimal Design and Control of Multibody Systems